Reusing Distance Courseware to Enable Blended Delivery: A New Zealand Case Study - Liam Atwood; Rachael Kelleher; Meryl Richards; Mark Nichols (Open Praxis)
Digital distance course materials can be used across different forms of education delivery. In particular, courseware designed for asynchronous digital distance education can serve as the basis for blended learning, which features a different teaching role and fuller interpersonal experience. Blended learning can be used to extend programme opportunities across population regions where a full, lecture-based model might not be viable. This case study explores the experiences of three regional polytechnics in New Zealand that adopted and modified courseware created for digital distance learners studying asynchronously. The courseware was used to provide local students with more flexible study options, drawing on high quality courseware that had been centrally created by a team of experienced courseware designers and Subject Matter Experts (SMEs).